Teenage mutant ninja turtles color classics (2012), volume 3 ebook - Eastman, Kevin (Teenage Mutant Ninja Turtles Color Classics (2012), 2015)
Go back to the very beginning, with the Turtles' first encounter with the Foot Clan and their mysterious leader, the Shredder. With over 300 pages of mutated martial-arts action, this volume is perfect for fans to relive the glorious days of the Turtles' origins, as well as an excellent place for new readers to see where the TMNT phenomenon began. Collects the first seven issues of the series, plus the Raphael and Michelangelo Micro-Series one-shots, all in brilliant color. Author: Kevin Eastman, Peter Laird. Illustrator: Kevin Eastman, Peter Laird. © 2018 Viacom International Inc. All Rights Reserved. TEENAGE MUTANT NINJA TURTLES and all related titles, logos and characters are trademarks of Viacom International Inc.